2019
DOI: 10.1007/978-3-030-34968-4_21
|View full text |Cite
|
Sign up to set email alerts
|

Isabelle/SACM: Computer-Assisted Assurance Cases with Integrated Formal Methods

Abstract: Assurance cases (ACs) are often required to certify critical systems. The use of integrated formal methods (FMs) in assurance can improve automation, increase confidence, and overcome errant reasoning. However, ACs can rarely be fully formalised, as the use of FMs is contingent on models that are validated by informal processes. Consequently, assurance techniques should support both formal and informal artifacts, with explicated inferential links between them. In this paper, we contribute a formal machine-chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It is likely that evidence that such systems behave as intended will be required for certification by regulators prior to deployment. Toward providing such evidence, Nemouchi et al have recently shown how a descriptive language for safety cases can be incorporated into Isabelle in order to formalize argument-based safety assurance cases [38].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that evidence that such systems behave as intended will be required for certification by regulators prior to deployment. Toward providing such evidence, Nemouchi et al have recently shown how a descriptive language for safety cases can be incorporated into Isabelle in order to formalize argument-based safety assurance cases [38].…”
Section: Discussionmentioning
confidence: 99%
“…The algorithm starts by restricting the traceability relation based on D, slices the original system model S using the elements deleted and modified as a slicing criterion, and slices the modified system model S using the added and modified elements as the slicing criterion (lines [16][17][18]. Using those two slices, the corresponding GSN model elements are traced using the traceability relation (line 19). The GSN elements traced from elements deleted from the original system model are to be revised (line 20).…”
Section: Single-product Algorithmmentioning
confidence: 99%
“…The seL4 microkernel [14] was verified using the Isabelle\HOL theorem prover. Isabelle was also used to formalize the Structured Assurance Case Metamodel (SACM) notation for certified definition of assurance cases [19].…”
Section: Related Workmentioning
confidence: 99%